Development and Validation of RP-HPLC Method for the Determination of Ganciclovir in Bulk Drug and in Formulations. (5th July 2012) - Ramesh, P. J.; Basavaiah, K.; Vinay, K. B.; Xavier, Cijo M.
Abstract : A simple, rapid, accurate, and precise gradient reversed-phase HPLC (RP-HPLC) method has been developed for the determination of ganciclovir (GNC) in pharmaceuticals. Chromatographic separation was carried out on inertsil ODS C18 (4.6 mmi .d × 250 mm, 5.0 μ m) LC column using ammonium acetate buffer, sodium salt of hexane sulfonic acid as ion-pairing reagent in 1000 mL water, and acetonitrile (90 : 10) (v/v) as mobile phase at a flow rate of 1.0 mL min − 1 and with UV detection at 245 nm at column temperature (30°C). The runtime under these chromatographic conditions was 10 min. The method was linear over the range of 0.02–75 μ g mL − 1 . The limits of detection (LOD) and quantification (LOQ) values were 4.1 and 20 ng mL − 1, respectively. The method was successfully extended to study the effect on GNC upon treatment with 2 N NaOH, 2N HCl, and 5% H2 O2 for 2 hrs at 80°C and upon exposure to UV (1200 K lux hrs) for 72 hrs and thermal (105°C) for 5 hrs. The proposed method was further applied to the determination of GNC in pharmaceuticals, with good percent recovery. The accuracy and the precision of the method were validated on intraday and interday basis in accordance with ICH guidelines.